Improving radar performance with constant envelope multi-level chirp - Farhad Bahadori-Jahromi (Tehnički Glasnik, 2019)
M-level Continuous Phase Chirp Modulation is considered for data transmission. In this article, we would like to propose a new approach to transmitting information with the help of multi-level wave guide signaling. The main problem with the classic chirp modulation system is that the final phase of the signal is not equal in each period to the initial phase of the next step, and this discontinuity is present in each data transmission period. The main objective of this paper is to improve the efficiency of chirp modulation, which is recommended for continuous phase multi-level scalar modulation, which results has a significant increase in system performance. In this new approach, for sending the M symbols, we use the M level to send the message. With the help of this idea, we simulate the telecommunication system and examine the probability of its bit error in the presence of additive white Gaussian noise and Rician fading.